Diary Media Towards Students’ Writing Recount Text - Oktaviani Oktaviani; Hastuti Retno Kuspiyah; Muhammad Muklas (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
This objective of this study was to know whether or not there are any significant differences between the students who are taught by using Diary media and the students who are taught by using conventional